Discourse of the Toxic Relationship: Violence Against Men from a Victim Precipitation Theory - Chazizah Gusnita; Riski Melinda (Soshum: Jurnal Sosial dan Humaniora, 2023)
The phenomenon of dating violence that resulted in teenage guys becoming victims is still tough to track down. Several causes contribute to violence, including social stereotypes, toxic masculinity, the criminal justice system's weakness, ignorance, and so on. This is what makes the individual in the case rude. Some of the crimes committed involved the victim, who in this case was a youngster who became a victim of violence and engaged in the commission of crimes done by his partner. Based on their involvement in a victim precipitation hypothesis, there are five sorts of victims: (1) nonparticipating victims; (2) latent or predisposed victims; (3) provocative victims; (4) participating victims; and (5) false victims. Based on her comments, the victim in this case fits four of the five criteria. The qualitative-descriptive method will be employed in this study to discuss the analysis of violence in dating that occurs against men.